The important role of inclusive education for the social interaction of students with special needs - ‘Aisy, Naurah Rohadatul; Aprilia, Imas Diana (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2025)
Inclusive education plays a crucial role in fostering social interaction among students with special needs. This study aimed to explore how inclusive education impacts the social development of children with disabilities through a systematic literature review. The research identified key benefits of inclusive education, including improved communication skills, stronger peer relationships, and enhanced self-esteem for students with special needs. Additionally, typically developing students also gained empathy and social awareness through inclusive settings. However, the study found significant challenges, such as social isolation, peer rejection, and inadequate teacher training, which hinder the effectiveness of inclusive education. The research emphasized the importance of targeted interventions, such as structured social skills programs and peer-mediated strategies, to improve the inclusion experience. Moreover, the voices of students with disabilities, particularly those with autism spectrum disorder, were found to be underrepresented in discussions about best practices, leading to ineffective inclusion strategies. This study highlights the need for better teacher preparation, increased social support, and student-centered policies to create a truly inclusive learning environment. By addressing these challenges, inclusive education can be a powerful tool for promoting social integration and equality in schools.